2014
DOI: 10.1111/aae.12044
|View full text |Cite
|
Sign up to set email alerts
|

Nabataean or not? The ancient necropolis of Dumat. First stage: a reassessment of al‐Dayel's excavations

Abstract: Nabataean or not? The ancient necropolis of Dumat. First stage: a reassessment of al-Dayel's excavations Two reports on excavations carried out in 1985-1986 by archaeologist Khaled Abdulaziz al-Dayel and published in the journal Atlal (1988Atlal ( , 1986 have revealed the existence of 'Hellenistic tombs' in the D umat al-Jandal oasis (ancient Adummatu/ Dumat/Dumata) in northern Saudi Arabia. Although attributed more precisely to the Nabataeans by Khalil al-Muaikel (1994), these tombs nevertheless appear not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Radiocarbon dating was undertaken on human bone from these cairns, revealing at least four periods of use (Figure 6 & OSM 1): Fifth millennium BC, between 4685 and 4075 BC.Second half of the fourth millennium BC to the second half of the third millennium BC (3485–2345 BC).Mid second millennium BC (between 1610 and 1435 BC).First millennium BC to the beginning of the first millennium AD (between 768 BC and AD 55).One radiocarbon date obtained on a charcoal sample from a cairn burial excavated on the promontory (Tomb L2204, SD31) suggests that it was used at the very end of the first millennium BC to the beginning of the first millennium AD, although the material found in the tomb could suggest an earlier date from the first half of the first millennium BC (Figure 10; see also OSM 1 & 4–5). Continuity in the use of the local funerary landscape is also noted for later periods, with evidence of a Nabataean–Roman necropolis inside the oasis (Figure 6; OSM 1; also see Charloux et al 2014).
Figure 10.Artefacts from tomb L2204, SD31: A) Dentalium sp.
…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Radiocarbon dating was undertaken on human bone from these cairns, revealing at least four periods of use (Figure 6 & OSM 1): Fifth millennium BC, between 4685 and 4075 BC.Second half of the fourth millennium BC to the second half of the third millennium BC (3485–2345 BC).Mid second millennium BC (between 1610 and 1435 BC).First millennium BC to the beginning of the first millennium AD (between 768 BC and AD 55).One radiocarbon date obtained on a charcoal sample from a cairn burial excavated on the promontory (Tomb L2204, SD31) suggests that it was used at the very end of the first millennium BC to the beginning of the first millennium AD, although the material found in the tomb could suggest an earlier date from the first half of the first millennium BC (Figure 10; see also OSM 1 & 4–5). Continuity in the use of the local funerary landscape is also noted for later periods, with evidence of a Nabataean–Roman necropolis inside the oasis (Figure 6; OSM 1; also see Charloux et al 2014).
Figure 10.Artefacts from tomb L2204, SD31: A) Dentalium sp.
…”
Section: Discussionmentioning
confidence: 71%
“…One radiocarbon date obtained on a charcoal sample from a cairn burial excavated on the promontory (Tomb L2204, SD31) suggests that it was used at the very end of the first millennium BC to the beginning of the first millennium AD, although the material found in the tomb could suggest an earlier date from the first half of the first millennium BC (Figure 10; see also OSM 1 & 4-5). Continuity in the use of the local funerary landscape is also noted for later periods, with evidence of a Nabataean-Roman necropolis inside the oasis ( Figure 6; OSM 1; also see Charloux et al 2014).…”
Section: Two Categories Of Archaeological Deposit Illuminate the Funcmentioning
confidence: 78%
“…The Camel Site is located 5–9km to the east of several Nabataean sites: al-Qal‘ah (DaJ16), Qârat al-Mazâd (DaJ156) and Sakâkâ (DaJ25) (Theeb [Dhuyayb] (al-) 2010: 891–929, 935) (Figure 3). Furthermore, study of the Dûmat al-Jandal necropolis has demonstrated the presence of Parthian objects dating to the turn of the first century BC/AD (Charloux et al 2014: 193–206). The mix of Nabataean and Mesopotamian influences in the representations at the Camel Site is consistent with the location of the Sakâkâ basin on a route between Transjordan and southern Mesopotamia, and on the fringes of the Roman trade routes (Charloux et al 2014: 208).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, study of the Dûmat al-Jandal necropolis has demonstrated the presence of Parthian objects dating to the turn of the first century BC/AD (Charloux et al 2014: 193–206). The mix of Nabataean and Mesopotamian influences in the representations at the Camel Site is consistent with the location of the Sakâkâ basin on a route between Transjordan and southern Mesopotamia, and on the fringes of the Roman trade routes (Charloux et al 2014: 208). Dûmat al-Jandal is, incidentally, often considered the eastern limit of the Nabataean kingdom and an important caravan staging post on the route leading to Mesopotamia and the Persian Gulf (Glueck 1944: 11–15; Sartre 2001: 20; Schmid 2007: 67–68).…”
Section: Discussionmentioning
confidence: 99%
“…Another characteristic common with Taymāʾ is the presence of elongated voids in the masonry of the ramparts in Dūmat (Charloux et al, 2014: fig. 20; Schneider, 2012: pl.…”
Section: Characteristics Of Regional Rampartsmentioning
confidence: 99%